2014
DOI: 10.5114/aoms.2014.40739
|View full text |Cite
|
Sign up to set email alerts
|

State of the art paper Influence of lifestyle on the course of type 1 diabetes mellitus

Abstract: Type 1 diabetes (T1DM) is an autoimmune disease that requires insulin treatment from the time of diagnosis. Its clinical course depends on both genetic and environmental factors, and the lifestyle of a patient modulates their interaction. The evidence about the influence of lifestyle on the course of T1DM is increasing. In this paper, we present evidence on the relationship between lifestyle parameters and diabetes-related outcomes. We discuss the most commonly addressed factors associated with lifestyle, such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 93 publications
(94 reference statements)
2
20
0
Order By: Relevance
“…She adheres to regular follow ups. Evidences of cases of type 1 diabetes due to disturbed lifestyle are increasing [13]. Dietary intervention is a great help to medical science in curbing type 1 diabetes in a higher percentage, without causing any side effects.…”
Section: Discussionmentioning
confidence: 99%
“…She adheres to regular follow ups. Evidences of cases of type 1 diabetes due to disturbed lifestyle are increasing [13]. Dietary intervention is a great help to medical science in curbing type 1 diabetes in a higher percentage, without causing any side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Pilacinski et al suggested a correlation between a lack of physical activity and type I diabetes. The researchers point out that exercise increases insulin sensitivity, which has beneficial effect on the patients [13]. …”
Section: Discussionmentioning
confidence: 99%
“…Insulin pump therapy is more effective and safer for maintaining glycemic control. It minimizes diabetes-associated complications, provides higher flexibility in daily life, and improves quality of life (13,16,17). Pumps provide an accurate history of insulin use through their menus and often this history can be uploaded and displayed as a graph for purposes of trend analysis.…”
Section: Discussionmentioning
confidence: 99%